Communication Flows in International Product Innovation Teams - Moenaert, Rudy K.; Caeldries, Filip; Lievens, Annouk; Wauters, Elke (The Journal of product innovation management, 2000)
Recently, we have witnessed a strong growth in the internationalization of many firms' product development activities. However, the lack of attention devoted by scientific research to the management of international innovation contrasts sharply with the importance attached to it as a cornerstone of international business success. Although several empirical studies and normative theories have specified the communication requirements in innovation teams, an empirically based insight is definitely needed on the communication requirements and requirements that prevail in the complex context of international innovation teams, in which the participants are located in different company units, countries, and cultures. This article addresses the following research question: viewing international innovation as an interfunctional activity, what are the communication requirements an international innovation team is facing, and what are the communication capabilities (interface mechanisms) that may be adopted to initiate, develop, and launch the new product effectively and efficiently? An extensive case study research project was designed to develop a comprehensive theoretical framework. Over a two year time period, the research team has investigated selected innovation projects in four European multinational corporations. The analysis of the case study data suggests five requirements that determine the effectiveness and efficiency of communication in international product development teams: network transparency, knowledge codification, knowledge credibility, communication cost, secrecy. To cope with these communication requirements, organizations may create firm level capabilities (parallel structures, cross‐functional and inter‐unit climate, communication infrastructure, goal congruence) and team level capabilities (core team, team leadership, formalization, procedural justice). The evidence from the in‐depth case study research indicates that these mechanisms provide a parsimonious and powerful approach to address the communication requirements in international product innovation teams. After the information processing framework proposed by Tushman and Nadler [124], the adoption of these mechanisms is expected to improve innovation effectiveness. This holds important consequences for the management of international product innovation projects. First, the innovating firm must balance centralization and decentralization, employ formal as well as informal strategies, and integrate ad‐hoc and permanent strategies. Second, it highlights the critical role of the project leader. Given the fact that companies often select the most available person, rather than the best person for the job, the allocation of light weight project leaders may create heavyweight problems in international teams. Third, following the argument in favor of procedural justice, the absence of involvement may severely hinder cross‐functional commitment to international innovation projects. Fourth, the innovating firm must also actively manage the communication flows with external parties. Failure to do so may result in flawed specifications, and a limited understanding about product design and market strategies.